Assessment Integrated with Learning of Mathematics at Elementary Stage - Rajput, Dr A. K. (THE PRIMARY TEACHER, 2012)
A paradigm shift is suggested in teaching processes at school levels in the National Curriculum Framework-2005. It is suggested that teachers should facilitate learning and should be able to create an environment for experiential learning. The learners in this era of technological advances have more number of learning resources in comparison to those just a decade ago. Children not only learn from the interactions that take place in the classroom, but also outside the classroom. So the learning takes place continuously as a result of interactions between the child and the environment provided. When learning is a continuous process and results after each and every experience that a child has, the assessment of learning should also be done continuously. In mathematics learning, it is more important as, by nature, mathematics is sequential, i.e., a concept cannot be learnt without understanding the prior related concepts. In present paper it is intended to give some ideas to teachers of elementary mathematics to integrate assessment with classroom interactions